Social Capital and Community Empowerment in Rural Development Programs: A Sociological Analysis - Nahri Idris; Layyinatus Shifah; Elinda Novita Dewi; Bustomi Bustomi; Putu Agus Ariana (Journal of Human Interaction and Social Studies, 2026)
We examine how social capital operates as a relational infrastructure shaping community empowerment within rural development programs through a multi-site qualitative case study grounded in interviews, focus groups, and observations. Findings show that empowerment emerges from dense interactional networks that connect bonding, bridging, and linking ties, enabling communities to negotiate power, institutional access, and collective learning. Gendered and livelihood-based networks function as critical arenas where trust and reciprocity are translated into durable participatory practices, while supportive governance arrangements stabilize these relational gains across time. Comparative analysis demonstrates that sustainable empowerment depends on balancing internal cohesion with external partnerships and institutional memory, producing adaptive capacities resilient to social and administrative change. The study advances a sociological model that conceptualizes social capital as a dynamic process linking interaction, power, and sustainability in rural contexts, and offers methodological insights for evaluating empowerment beyond output-centered metrics. By foregrounding relational mechanisms, the research clarifies how community agency is continuously reproduced through negotiated networks that integrate institutional credibility with everyday cooperation, informing more inclusive and durable